Planning for international business negotiation - Kapoor, Ashok (Cambridge, Mass., Ballinger Pub. Co., 1975)
The book examines the process of planning for international business negotiation and covers topics like nature of negotiation, reasons for negotiation among others. Others include: negotiation for international mixed venture; Mitsubishi-Chrysler Automobile joint venture negotiation for entry into Japan; OPEC-oil companies negotiation team in Teheran.
Includes index.
Includes bibliographical references: p. 339-350.
lje 19/04/2018
Loans
Keywords: International business enterprises; Investments, Foreign; Negotiation in business